Development of Reasoning Multiple Choice Questions (RMCQs) to Analyze Higher Order Thinking Skills - Diah Ayu Saputri; Mohammad Masykuri; Suryadi Budi Utomo (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
The development of reasoning multiple choice questions (RMCQs) to analyze higher-order thinking skills is based on the need for appropriate assessment instruments to determine high-order thinking skills on learning requirements in the 21st century. The development used the model proposed by Thiagarajan, 4D-models with four process stages: (1) define; (2) design; (3) develop; (4) disseminate. The results were analyzed using the winstep application to obtain the value of validity, reliability, discriminatory power, distractor index, and difficulty level. The instrument has a good reliability coefficient, shown by the item reliability in the final test of 0.98, with the ability to distinguish three groups of samples, low, moderate, and high. 75% of the validity index and 80% of the distractor index function well, so the assessment instrument developed can be used to analyze high-order thinking skills. The assessment instrument is also applicative if used as an evaluation instrument in chemistry learning.